2022
DOI: 10.1212/wnl.0000000000013055
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds and Treatment Effect of Intravenous Thrombolysis in Acute Stroke

Abstract: Background and ObjectivesCerebral microbleeds (CMBs) are common in acute ischemic stroke patients and are associated with increased risk of intracerebral hemorrhage (ICH) after intravenous thrombolysis. Whether CMBs modify the treatment effect of thrombolysis is unknown.MethodsWe performed a pre-specified analysis of the prospective randomized controlled multicenter WAKE-UP trial including patients with acute ischemic stroke with unknown time of symptom onset and DWI-FLAIR mismatch on MRI receiving alteplase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…The results of this study do not suggest absence of treatment effect of EVT in the high CMB population, and should not be used as evidence for excluding patients from a powerful treatment modality. A recent study using data from a randomized IV thrombolysis has shown no reduced treatment effect of alteplase in acute ischemic stroke patients with one or more CMBs 33 , while reaching inconclusive conclusions regarding larger numbers of CMBs. Similarly designed studies will be needed regarding EVT treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study do not suggest absence of treatment effect of EVT in the high CMB population, and should not be used as evidence for excluding patients from a powerful treatment modality. A recent study using data from a randomized IV thrombolysis has shown no reduced treatment effect of alteplase in acute ischemic stroke patients with one or more CMBs 33 , while reaching inconclusive conclusions regarding larger numbers of CMBs. Similarly designed studies will be needed regarding EVT treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were followed up via telephone, and a total of 34 patients with valid information were included. Outcomes were assessed based on the mRS, with an mRS ≤ 1 defined as good recovery [ 17 ]. Mental status was assessed using the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), and Hamilton Depression Scale (HAMD).…”
Section: Methodsmentioning
confidence: 99%
“…Seizures that occurred before admission were recorded based on witness descriptions. NIHSS and mRS scores at admission were recorded to assess stroke severity in patients with CVST ( 12 , 13 ). Laboratory data were available for each patient at admission as part of an emergency or routine admission checkup.…”
Section: Methodsmentioning
confidence: 99%